The role of patient-related factors in the implementation of a multimodal home-based rehabilitation intervention after discharge from inpatient geriatric rehabilitation (GeRas): a qualitative process evaluation - Maier, Leonie; Benzinger, Petra; Abel, Bastian; Roigk, Patrick; Bongartz, Martin; Wirth, Isabel; Cuvelier, Ingeborg; Schölch, Sabine; Büchele, Gisela; Deuster, Oliver; Bauer, Jürgen M.; Rapp, Kilian; et al. (European geriatric medicine, 2024)
The aim was to explore how patient-related factors influence the implementation of the geriatric rehabilitation aftercare program GeRas from the perspectives of patients and Healthcare providers.